Estratégias funcionais das espécies dominantes na sucessão florestal na Amazônia Central - Fernandes Neto, José Guedes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
The study of the functions performed by species in plant communities makes an important contribution to understanding the dynamics of communities and their effects on ecosystem functioning. Thus, community assembly patterns may be better understood in this functional perspective when compared to a strictly taxonomic perspective and comparisons between regions and biomes become feasible through the functional traits. The functional traits dynamics along secondary succession is a good opportunity to analyze the communities’ assemblies in face the ecological factors that cause these forests. The role of dominant species is crucial in this process because they reflect the responses to disturbances and contribute to the initial dynamics of ecosystem functioning. Thus, this study analyzed the functional traits dynamics of the dominant species in two successional trajectories in secondary forests north of Manaus. For this, the data collected over 14 years by Projeto Pioneiras at Biological Dynamics of Forest Fragments Project were used to calculate the dominant species in basal area in the forests converted to pasture (FCP) and the clear-cut vegetation forest (FCR). Leaf area, Leaf Dry Mass Content, Specific Leaf Area and Wood Density were the functional traits collected for 167 individuals of 26 species and had their community weighted mean (CWM) calculated according to basal area in the year evaluated for each transect. The height and diameter at breast height were also collected and the Seed Weight was obtained through literature. In FCP was obtained only one significant relationship to the succession of time: the CWM – Wood Density. For FCR CWM - Leaf Area, Leaf Dry Mass Content, Specific Leaf Area and Seed Weight had significant relationships varying with the line slope. The functional trajectory of transects shows that clear cut forests have a greater extent than the forest derived from pasture and an apparent directionality in succession. The functional richness (FRic) showed no significant difference between the areas, but this is marginally significant (t = 2.0504, p = 0.0659). These results corroborate other studies on the possibility of succession lying arrested in forests derived from agricultural activity, which can result in loss of species and functional diversity, forest's resilience to support future impacts and its ecosystem services declining in quality.
Keywords: Espécies pioneiras; Floresta secundária